Internal anatomy of Hypochthonius rufulus (acari: Oribatida) - Smrž, Jaroslav (Journal of morphology, 1989)
The internal anatomy of juveniles and adults of Hypochthonius rufulus selected as a model species representing the lower Oribatida was investigated histologically and compared with the published characteristics of higher oribatid internal anatomy. In this species, the cuticle is weak and flexible, consisting of epicuticle and endocuticle on the body, but including an exocuticle between the epicuticle and endocuticle of the legs. Walls of the mesenteron in the digestive tract are of uniform thickness and structure without any regional thickening, and there are no proventricular glands. The hindgut is apparently divided into five parts: colon 1 and 2, rectum 1 and 2, and anal atrium; food bolus exhibits a multilamellar structure in this section. The glandular system is less diversified than in some other oribatids. Tracheae are apparently lacking. Females possess only two relatively large eggs, filling one-half of opistosoma, and they lack ovipositors. Eggs are present in females during the whole year. Gonad buds appear first in the protonymph stage. Only one male was found among 146 adults studied. No male external organ (aedeagus or penis) is present.